State Dependent Riccati Equation (SDRE) control method applied in cancellation of a parametric resonance in a magnetically levitated body - Chavarette, Fábio Roberto [UNESP]; Balthazar, José Manoel [UNESP]; Dos Reis, Célia Aparecida [UNESP]; Peruzzi, Nelson José [UNESP] (ASME International, 2011)
Here, a simplified dynamical model of a magnetically levitated body is considered. The origin of an inertial Cartesian reference frame is set at the pivot point of the pendulum on the levitated body in its static equilibrium state (ie, the gap between the magnet on the base and the magnet on the body, in this state). The governing equations of motion has been derived and the characteristic feature of the strategy is the exploitation of the nonlinear effect of the inertial force associated, with the motion of a pendulum-type vibration absorber driven, by an appropriate control torque [4]. In the present paper, we analyzed the nonlinear dynamics of problem, discussed the energy transfer between the main system and the pendulum in time, and developed State Dependent Riccati Equation (SDRE) control design to reducing the unstable oscillatory movement of the magnetically levitated body to a stable fixed point. The simulations results showed the effectiveness of the (SDRE) control design. Copyright © 2011 by ASME.
Keywords: Cartesians; Control design; Control methods; Control torque; Dynamical model; Governing equations of motion; Inertial forces; Nonlinear effect; Oscillatory movements; Parametric resonance; Pivot point; Reference frame; Stable fixed points; State-dependent Riccati equation; Static equilibrium state; Vibration absorber; Control; Design; Dynamics; Energy transfer; Equations of motion; Magnets; Pendulums